2016
DOI: 10.1093/gji/ggv513
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation seismic experiments – II: wide-angle, multi-azimuth, 3-D, full-waveform inversion of sparse field data

Abstract: S U M M A R Y3-D full-waveform inversion (FWI) is an advanced seismic imaging technique that has been widely adopted by the oil and gas industry to obtain high-fidelity models of P-wave velocity that lead to improvements in migrated images of the reservoir. Most industrial applications of 3-D FWI model the acoustic wavefield, often account for the kinematic effect of anisotropy, and focus on matching the low-frequency component of the early arriving refractions that are most sensitive to P-wave velocity struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…It is likely that our 2‐D imaging has been hampered by 3‐D effects due to the complex geology of the eastern Nankai Trough. This raises the issue of how to design the next generation of 3‐D dense sea bottom acquisitions for deep crustal investigations [ Morgan et al , , ]. Although various advances have been achieved in seismic instrumentation and the ability of the academic community to perform OBS acquisitions is increasing, the gathering of large OBS pools remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that our 2‐D imaging has been hampered by 3‐D effects due to the complex geology of the eastern Nankai Trough. This raises the issue of how to design the next generation of 3‐D dense sea bottom acquisitions for deep crustal investigations [ Morgan et al , , ]. Although various advances have been achieved in seismic instrumentation and the ability of the academic community to perform OBS acquisitions is increasing, the gathering of large OBS pools remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The models are characterized by low velocities at the segment ends relative to the segment center that were interpreted in terms of increased fracturing in the upper crust created near the OSCs and possibly less hydrothermal infilling of porosity. More recently Morgan et al [] have used full‐waveform inversions to improve the resolution of shallow upper crustal structure in the central portion of the experiment footprint.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Kamei et al (2012) applied frequency-domain FWI to a separate deployment of 54 OBS at the Nankai trough, resolving the fine scale velocity structure of megasplay faulting. Recently, Morgan et al (2016) demonstrated the application of three-dimensional (3D) time-domain FWI on an array of 21 OBS situated across the Endeavour oceanic spreading centre of the Juan de Fuca Ridge, revealing lowvelocity zones interpreted to represent a magmatic-hydrothermal reaction zone (Arnoux et al 2017). These studies have made use of relatively dense OBS deployments (~ 1 km spacing), or a 3D seismic shooting configuration, both of which are not always possible in academic experiments.…”
Section: Introductionmentioning
confidence: 99%